Perlindungan Hukum Dan Jaminan Sosial Bagi Pekerja Migran Di Indonesia Menurut Hukum Positif Indonesia - Bayu Prawira Putra Haryawan; Any Suryani Hamzah (Fakultas Hukum Universitas Mataram, 2022)
This study aims to determine the legal protection and social security for migrant worker in Indonesia under Indonesia positive law and to determine the protections for migrant worker in their occupancy period. This study using normative method, and using qualitative analyze method. Result of this study showed that one of the efforts of Indonesia government to protect migrant worker is giving social security for migrant worker pursuant to Indonesian law. This social security given to the migrant worker in their occupancy period.